COVID-19 and specialty crop producers: economic impacts and grower solutions - Richard Volpe; Xiaowei Cai; Timothy Delbridge; Alexander Stevens (Agricultural and Resource Economics Review)
We use a combination of primary and secondary data to investigate and quantify the impacts of the COVID-19 pandemic on the California specialty crop sector. We demonstrate that the specialty crop sector was highly resilient during the pandemic and aftermath in terms of output. For many crops, production fell somewhat between 2019 and 2021, but not to an extent that is outside of normal annual variation for fruits and vegetables. However, prices increased dramatically for many commodities. Contrary to conventional wisdom, most input costs did not surge during the pandemic, and some fell. But both the primary and secondary data identify labor and truck transportation as the major issues facing producers and driving up prices. Trade associations played a vital role in disseminating solutions to growers throughout the pandemic.